Eating habits matter for sleep difficulties in children and adolescents: A cross-sectional study - Zhao, Yaping; Qu, Diyang; Liang, Kaixin; Bao, Ran; Chen, Sitong (Frontiers in Pediatrics, 2023)
Abstract Background: Sleep difficulties are a common sleep-related issue among children and adolescents. However, the association between eating habits and sleep difficulties has not been extensively studied. Therefore, this study aimed to investigate the relationship between eating habits and sleep difficulties in children and adolescents, thereby contributing to our knowledge in this important area. Methods: This study utilized cross-sectional data from the 2013/2014 Health Behavior in School-aged Children survey. A total of 213,879 young adolescents provided self-reported information on their weekday and weekend breakfast consumption, fruit and vegetable intake, sweet and soft drink consumption, and sleep difficulties. Covariates such as sex, age, family affluence, physical activity, and body mass index were also considered. Multilevel generalized linear modeling was used to analyze the associations between the independent and dependent variables. The results were reported as odds ratios (OR) and 95% confidence intervals. Results: Of all study participants, approximately 50% were girls. Regression models indicated that more frequent breakfast consumption was associated with fewer sleep difficulties (e.g., consuming breakfast on weekdays for five days: OR = 1.49, 95% CI: 1.45–1.54). Fruit and vegetable consumption once a week or more was also linked to fewer sleep difficulties (all OR > 1.08, p < 0.005). Similarly, consuming less sweets and soft drinks was generally associated with fewer sleep difficulties. Conclusion: This study provides evidence supporting the association between healthier eating habits and reduced sleep difficulties in children and adolescents. Future research using longitudinal or experimental designs is encouraged to confirm or challenge these findings. Additionally, this study offers practical guidance for nutritional counseling professionals and sleep health promotion practitioners in their respective fields.